Elevated interleukin-37 associated with tophus and pro-inflammatory mediators in Chinese gout patients. (May 2021) - Ding, Liping; Li, Heng; Sun, Baodong; Wang, Tingting; Meng, Shuhui; Huang, Qin; Hong, Xiaoping; Liu, Dongzhou
Highlights: IL-37 was significantly increased in active gout patients with tophus. No significant difference in IL-37 level between hyperuricemia and normal controls. IL-1β, IL-6 and IL-18 levels were significant elevated in gout patients with tophus. IL-37 was positively correlated with CRP and ESR, as well as IL-1β, IL-6 and IL-18. IL-37 was a potential marker for the tophus formation in gout. Abstract: Introduction: Interleukin-37(IL-37), a natural inhibitor of innate immunity, has been identified to protect against various inflammatory diseases, including monosodium urate (MSU)-induced inflammation. However, the association of IL-37 with clinical indexes and pro-inflammatory mediators in gout patients remains unclear. The aim of this study was to determine IL-37 level in hyperuricemia and gout patients with or without tophus, and to investigate the correlations of IL-37 with clinical indexs such as Uric Acid (UA), CRP(C-reactive protein), Creatinine Clearance Rate (Ccr), Erythrocyte Sedimentation Rate (ESR) and so on, as well as with the pro-inflammatory mediators in serum including Interleukin-1β(IL-1β), Interleukin-6(IL-6) and Interleukin-18(IL-18) from gout patients. Methodology: The serum levels of IL-37, IL-1β, IL-6 and IL-18 levels in serum of gout patients were determined by ELISA; the correlations between IL-37 and clinical values or pro-inflammatory mediators in serum of gout were analyzed by Spearman correlation test. Results: The serum levels of IL-37 were higher in active gout patients than inactive gout patients and HCs, especially in active gout patients with tophus. No significant difference was observed in serum IL-37 levels between hyperuricemia and normal controls. IL-1β, IL-6 and IL-18 levels were significant elevated in gout patients with tophus than those without tophus; Serum IL-37 were positively correlated with CRP and ESR, as well as with IL-1β, IL-6 and IL-18, negatively correlated with Ccr, and not correlated with UA, creatinine (Cr) and triglyceride (TG) in gout patients. Conclusions: IL-37 increased in gout patients positively associated CRP and ESR, as well as with proinflammatory mediators IL-1β, IL-6, IL-18, the presence of tophus and chronic kidney disease in gout. It may be a novel marker for predicting this pathology.